Experimental analysis of the effect of the structure area on the PZT-based SHM systems - Baptista, Fabricio Guimaraes [UNESP]; Vieira Filho, Jozué [UNESP]; Turra, Antonio Eduardo [UNESP]; Lopes Jr., Vicente [UNESP] (ASME International, 2009)
The structural health monitoring (SHM) systems based on electromechanical (E/M) impedance technique have been widely investigated. Although many studies indicate the reliability of this technique, some practical considerations still have to be considered in real applications. This paper presents an experimental analysis of the effect of the structure area on the system's performance. The results indicate that the sensitivity of the system to detect damage decreases significantly when the host structure has large cross-section area. Copyright © 2009 by ASME.
Keywords: Cross-section area; Experimental analysis; Host structure; Impedance techniques; PZT; Real applications; System's performance; Intelligent materials; Intelligent systems; Structural health monitoring